Vold som udtryksform i fagprofessionel praksis - Marie Østergaard Møller (Tidsskrift for Professionsstudier, 2024)
What happens in the encounter between system and client when social interaction is expressed as violence? While research has focused on citizen consequences of system power, regulatory challenges in the system's encounter with resourceful citizens and on professional consequences of stereotypical understandings of citizens, we know less about the extent, type and consequences of violence perpetrated against professionals. The article focuses on violence prevention within the welfare areas of employment, health and social security and is based on the results of a literature review (111 studies) of type II violence (citizen violence against professionals). The analyses present indicators, consequences and solutions to violence and show that violence can reduce the employee's judgment, job satisfaction and increase the risk of changing jobs. The professional may experience a general fear for their own safety and an increased risk of stress, including PTSD, just as the violence may have consequences for the employee's professional judgments. Judgment may in some cases be temporary and other times permanently threatened, typically in connection with persistent, increased aggression in the workplace. The article describes the identification of risks, consequences and prevention of violence and points to future questions in studies of violence in professional practice.